2022
DOI: 10.3390/ma15207165
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Mechanical Properties of Basalt Fiber Reinforced High-Performance Concrete Using Machine Learning Techniques

Abstract: In this research, we present an efficient implementation of machine learning (ML) models that forecast the mechanical properties of basalt fiber-reinforced high-performance concrete (BFHPC). The objective of the present study was to predict compressive, flexural, and tensile strengths of BFHPC through ML techniques and propose some correlations between these properties. Moreover, the modulus of elasticity (ME) values and compressive stress–strain curves were simulated using ML techniques. In this regard, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…With the drop weight test device with repeated blows, the number of blows to create a certain level of rupture is obtained, which is a measure of the material's energy absorption capacity. This test is performed by dropping a 4.54 kg weight from a height CONSTRUCTION MATERIALS AND PRODUCTS of 457 mm and repeated blows until certain cracking levels (first cracking and final cracking) continue [25][26][27][28]. 6 This test was carried out on concrete samples with disk dimensions of 15×16.36 cm obtained from concrete based on blast furnace slag treated at ambient temperatures of 25 and 90 °C at the age of 28 days and also based on equation (1) The impact energy absorption capacity E was calculated as…”
Section: Experiments Methodsmentioning
confidence: 99%
“…With the drop weight test device with repeated blows, the number of blows to create a certain level of rupture is obtained, which is a measure of the material's energy absorption capacity. This test is performed by dropping a 4.54 kg weight from a height CONSTRUCTION MATERIALS AND PRODUCTS of 457 mm and repeated blows until certain cracking levels (first cracking and final cracking) continue [25][26][27][28]. 6 This test was carried out on concrete samples with disk dimensions of 15×16.36 cm obtained from concrete based on blast furnace slag treated at ambient temperatures of 25 and 90 °C at the age of 28 days and also based on equation (1) The impact energy absorption capacity E was calculated as…”
Section: Experiments Methodsmentioning
confidence: 99%
“…Also popular is the Support Vector Regression (SVR) method, which is quite often used to assess the properties of building composites. For example, in studies [19], the SVR method was used to assess the durability of high-performance basalt fiber reinforced concrete and showed fairly high accuracy. Similarly, in research [20][21][22][23][24], this machine learning method makes it possible to quite accurately predict the concrete characteristics by including various additives (fly ash, microsilica) and subject to various types of impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that SVR had an acceptable predictive capacity. SVR was used by Hasanzadeh et al [36] to estimate the compressive, flexural, and tensile strengths of basalt-fiber-reinforced concrete. This conventional machine learning technique was also used to simulate the modulus of elasticity and compressive stress-strain curves.…”
Section: Introductionmentioning
confidence: 99%